Keterbukaan Informasi Dinas Dukcapil Kabupaten Bengkulu Tengah Dalam Pembuatan e-KTP - Bagiantin Mulya; Sapta Sari; Yanto Yanto (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The importance of a democratic country that upholds people's sovereignty which basically aims to realize good governance in the process of making KTPs at the Office of Population and Civil Registration. This study aims to determine the management of Public Information Disclosure at the Central Bengkulu Civil Registry Service in making e-KTPs. This study uses the Dipopramono theory in Law Number 14 of 2008 concerning Public Information Disclosure and the type of research used is qualitative research. The results of this study indicate that there are 3 things that support the disclosure of information at the Central Bengkulu Dukcapil Service in the Making of E-KTP, namely the first, information that must be provided and announced periodically that the announcement of the dukcapil information is conveyed to the village head who gets a circular letter given by the dukcapil to the head villages in the Central Bengkulu region, Facebook social media, whatsapp groups, and through the website, secondly, information that must be announced evenly that it is carried out with fast and targeted action so that in terms of the needs needed by the community can be realized properly, provision services are carried out quickly and evenly through social media, dukcapil info and the Central Bengkulu dukcapil telephone number which can be accessed via the website, the third is information that must be available at any time that this information applies through circular letters delivered by dukcapil to the Central Bengkulu district village head, the media social, wa groups, websites and direct actions of officers at the Central Bengkulu dukcapil office, which means that dukcapil information service actions are available at any time, so that the public does not have to worry about this information not being available because dukcapil information can be accessed through social media circulars, wa groups, websites and You can go directly to the Central Bengkulu Civil Registry Office